Exploring Elementary School Students' Perceptions toward Simulation-based Mobile Learning based on Predict-Observe-Explain Approach (International Conference on Computers in Education, 2016)
With a mobile device in hands, mobile learning serves to provide new learningopm»rtunities to individuals and it fits with many learning environments, both in classroomsetting and in informal learning environments. Recently, researchers have an interest in usingmobile technologies and simulations to deliver more effective learning experience to students.This presents an exploration of elementary school students' towardsimulation-based mobile learning based on predict-observe-explain (POE) instructionalsequence in a physical science lesson of light refraction. A total of ten 4th grade students wasrecruited to participate in this study. They were administered with 21 items of 5-points Likertscale perception questionnaire regarding six perceptual constructs, i.e. perceived learning(PL), perceived ease of use (PEU), flow (FL), IRrceived usefulness (PL]), enjoyment andperceived satisfaction (PS), after interacting with the approach. The result indicated that therewas some high degree of positive perceptions toward the approach, and the highest percentageof their perceptions were PU, E, PS, FL, PL, and PEU, respectively. Based on the finding, thesimulation-based mobile learning based on POE approach will be redesigned for enhancingstudents' learning performance in the next study.